Les poilus parlaient patois - Jean-Baptiste Martin (Lengas)
Documents in occitan or in francoprovençal essentially written about and during the 1914-1918 war are very few. An in-depth research resulted in the collection of about fourty of them in the Rhône-Alpes region. This wide range of texts (letters, poems, dramas, patriotic songs, prose) brings a new perspective on the Great War.